Global markets, national tax systems, and domestic politics: Rebalancing efficiency and equity in open states' income taxation - Steffen Ganghof (Max-Planck-Institut für Gesellschaftsforschung, 2001)
Competitive pressure on some capital income tax rates reinforces a generic quadrilemma or a four-way tradeoff in domestic income taxation. To maintain competitiveness, governments have to cut some tax rates on capital income down to international standards. If these cuts lead to a de-alignment of different rates on capital income, domestic allocation becomes more inefficient, all else being equal. Cutting all tax rates on capital income to a uniform low level, while maintaining high and progressive tax rates on labor incomes, avoids this inefficiency, but sacrifices comprehensive income taxation, that is, joint and equal taxation of capital and labor incomes. Finally, reducing all income tax rates to international standards, including top rates on labor income, implies a strong significant reduction in the progressiveness of labor income taxation (and/or significant revenue losses). As a result, governments that aim at all four goals - competitiveness, allocative efficiency, horizontal equity (comprehensive income taxation) and progressivity - and want to maintain a given revenue level cannot avoid seriously compromising one of them. This paper analyzes how this income tax quadrilemma has played out in seven OECD countries: Australia, Denmark, Finland, Germany, New Zealand, Norway, and Sweden. Combining the results of this matched comparison with exploratory data analysis for all OECD countries, the paper discusses the general implications of the quadrilemma for the domestic political economy of tax competition and the future of domestic compensation in open states. – – Der Wettbewerbsdruck auf einen Teil der Steuersätze auf Kapitaleinkommen verstärkt ein prinzipielles Quadrilemma, d.h. einen vierseitigen Zielkonflikt, in der innerstaatlichen Einkommensbesteuerung. Regierungen müssen einige Steuersätze auf Kapitaleinkommen senken, um wettbewerbsfähig zu bleiben. Wenn diese Satzsenkungen zu einer zunehmenden Spreizung zwischen Steuersätzen auf unterschiedliche Kapitaleinkommen führt, verringert sich, ceteris paribus, die Allokationseffizienz der innerstaatlichen Kapitaleinkommensbesteuerung. Dies wird vermieden, wenn alle Steuersätze auf Kapitaleinkommen auf ein einheitliches, wettbewerbsfähiges Niveau gesenkt und gleichzeitig höhere und progressive Steuersätze auf Arbeitseinkommen beibehalten werden; jedoch wird damit das Prinzip der synthetischen Einkommensbesteuerung aufgegeben, nach dem alle Arten von Einkommen gemeinsam und gleichmäßig zu besteuern sind. Werden schließlich alle (Spitzen-)Steuersätze der Einkommensteuer auf ein wettbewerbsfähiges Niveau gesenkt, führt dies zu einer Verringerung der (direkten) Progressivität der (Arbeits-)Einkommensbesteuerung - und/oder zu erheblichen Ausfällen bei den Steuereinnahmen. Regierungen können deshalb bei einem gegebenen Steueraufkommen nicht alle vier Ziele - Wettbewerbsfähigkeit, Allokationseffizienz, synthetische Einkommensbesteuerung und direkte Progressivität - in vollem Umfang erreichen. Der Beitrag zeigt, welche Rolle dieses grundlegende Quadrilemma der Einkommensbesteuerung in sieben OECD-Ländern gespielt hat: Australien, Dänemark, Deutschland, Finnland, Norwegen, Neuseeland, Norwegen und Schweden. Auf der Grundlage dieses Fallvergleichs und einer explorativen Datenanalyse für 21 OECD-Länder werden Schlussfolgerungen gezogen für innerstaatliche politische Ökonomie der Einkommensbesteuerung.
Keywords: 300; Kapitalertragsteuer; Steuerwettbewerb; Einkommensteuer; Besteuerungsgrundsatz; Wirtschaftspolitisches Ziel; Public Choice; OECD-Staaten